Activation of rubber-seed shell waste by malic acid as potential CO2 removal: Isotherm and kinetics studies - Borhan, A. (MDPI AG, 2020)
Carbon dioxide (CO2) has been deemed a significant contributor to the climate crisis and has an impact on environmental systems. Adsorption is widely used among other technologies for carbon capture because of its many benefits. As a starting material for the production of activated carbon (AC) by chemical activation using malic acid due to its biodegradable and non-toxic properties, rubber seed shell (RSS) was used as agricultural waste from rubber farming. Sample A6, which was carbonized for 120 min at a temperature of 600â¦C and impregnated at a ratio of 1:2, was identified to achieve the highest surface area of 938.61 m2 /g with micropore diameter of 1.368 nm, respectively. Using the fixed volumetric approach measured at 25, 50, and 100â¦C, the maximum CO2 adsorption capability reported is 59.73 cm3 /g of adsorbent. Using the pseudo-first order of Lagergren, the pseudo-second order and the Elovich model, experimental data is modeled. It appears that, based on the correlation coefficient, the pseudo-first order model is aligned with the experimental findings. Furthermore, the activation energy of under 40 kJ/mol indicated a physical adsorption occurs, indicating that the RSS chemically activated with malic acid is a fascinating source of CO2 removal requirements. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.